Role of Optimism on Employee Performance and Job Satisfaction - Mishra, Uma Sankar; Patnaik, Subhendu; Mishra, Bibhuti Bhusan (Prabandhan: Indian Journal of Management, 2016)
The aim of this study was to examine the role of optimism in employee performance and job satisfaction. Optimism is a positive psychological construct popularized by Martin Seligman. An optimist person has positive expectations and follows a positive attribution style. An individual possessing the psychological resource of optimism tends to face life with a positive view. But on the other hand, those persons who are pessimistic in nature view life events negatively. This study was conducted on a sample of 346 employees from three large public sector banks situated in the Eastern part of India. Correlation, regression, and structural equation modeling (SEM) techniques were used to test the hypotheses. Results depicted that optimism is positively related to employee performance and job satisfaction. This study also supported the external validity of optimism construct with relation to performance and job satisfaction in the Indian cultural context.